The implementation of Asean GAqP in overcoming Al-Jallalah related issues; with the focus on shariah-compliant and sustainability elements - Kartika, Betania; Parson, Sitti Walida; Jamaludin, Mohammad Aizat; Nordin, Noor Faizul Hadry; Chowdhury, Ahmed Jalal Khan; Pawenang, Supawi (2019)
Al-Jallalah is an Arabic term referring to animals that are consuming something filthy, such as feces and carcass, thus creating the foul smell and bad taste to the animal’s meat. In aquaculture practice, there are a series of cases reported by the media regarding improper feeding practice by some aquaculture farmers who use pig offal and carcass as feeding for the fish. This has raised concern among the Muslims because in Shariah point of view, consuming the meat of al-Jallalah animal is prohibited due to its filthiness that can cause detrimental to human health. This paper discusses the elements in Asean Good Aquaculture Practice (GAqP) which will be used to overcome the al-Jallalah related issues. Four elements namely food safety, animal health and welfare, environmental integrity and socio-economic aspect are discussed with the integration of Shariah perspective. The methodology used is the library research from various reliable sources, such as database and search engine that cover selected journals and information regarding the subject matters, including references from local or international fisheries authorities: Department of Fisheries Malaysia, Asean GAqP, Food, and Agriculture Organization of The United Nation, World Fish Center and Agriculture, Fisheries and Conservation Department of Hong Kong. The synthesized findings from this paper will provide a clear view of how GAqP is able to overcome the problems regarding al-Jallalah in aquaculture practice. Since GAqP is a voluntary scheme, for future undertaking the authorities are emphasized to start the action to litigate this scheme to become compulsory to resolve this issue completely. I